Forensic Investigation of Digital Evidence on Flash Disk with Forensic Process Method Based on NIST - Febriand Gysberth Pariela Zamsari; Teguh Wahyono (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
Flash disk is a tool that is inseparable from daily life. With flash disks, users can keep important data for personal or company. Apart from that, in lots of cases Indonesian law uses flash disks as evidence. ITE Law (Law Information and Transactions Electronics) regulates how the provision of digital evidence becomes strong evidence in court.​ This research investigates forensics to digital evidence on a flash disk with four scenario tests. Processing digital forensics uses a forensic process based on guide National Institute of Standards and Technology (NIST). This research produces an analysis where the evidence processed with scenarios 1 and 4 are valid digital evidence to be submitted to the court, while evidence 2 and 3 are invalid evidence.